HPLC determination of encapsulated 5-fluorouracil in lyoiphilized liposomes - Irena Stojanovska; Suzana Trajkovic-Jolevska; Aneta Dimitrovska (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2003)
5-fluorouracil is used as an antineoplastic agent in the treatment of several malignant neoplasm, alone or in a combination with other antineoplastic drugs. Due to the difficulties in delivery of antineoplastic drugs on the target place, serious adverse events and hazardous effects, recent advanced researches are focused on the topical colloidal systems as drug carriers for the chemical substance. Colloidal drug carriers, as liposomes, can improve the therapeutic effects of the chemical substances by modifying their distribution and increasing their efficacy. The aim of this study was to develop HPLC method for quantitative determination of encapsulated 5-fluorouracil in lyophilized liposomes. HPLC method was developed using the following chromatographic conditions: column- LiChrospher 60, RP Selected B, 125 x 4 mm, 5 µm; mobile phase - 0.02 M phosphate buffer pH 4.7; flow rate of 1.0 ml/min; column temperature 20 ºC; UV - detection at 266 nm; injection volume - 20 µl. Linear relationship was obtained in the concentration range of 10-100 µg/ml, r=0.9999. Accuracy of the method was confirmed by standard addition method. Determination of encapsulated 5-fluorouracil in lyophilized liposomes was carried out with RSD of 0.71 %. The proposed method could be used for rapid and precise quality control of lyophilized liposomes with 5-fluorouracil, used as drugdelivery system, prepared for further incorporation in pharmaceutical dosage form-gel.